La inadmisión de la acción por daño moral, por falta de legitimación activa, en los procesos ordinarios - Córdova Camacho, Leila Esthefanía (2018)
The present case study is of civil matter, initiated on August 26, 2013, by ordinary way, cause number 07456-2013-0722, action of moral damages, followed by Mr. Marlon Eduardo Aguilar Fallan against Mrs. María Eugenia Gutiérrez Giraldo, the main objective of this titling work is the lack of active legitimacy that existed on the part of the plaintiff since he did not have to act in the process, let alone request a pecuniary compensation for Four hundred ninety thousand United States of America dollars of America (USD 490.00.00) for moral damages against Mrs. María Eugenia Gutiérrez Giraldo. Because the journalistic note mentioned by the distinguished Semanario did not refer to his person, since the newspaper's note referred to Mr. Marlon Eduardo Aguilar Fallan, Mr. M. Eduardo Aguila with Mrs. María Eugenia Gutiérrez Giraldo by public deed granted at the Notaria Quinta del Cantón Machala, on September 28, 2011, and registered in the registry of the property of Machala, on December 15, 2011, they entered into a contract of sale promise for the amount of $ 116,099.40 payable in installments of lots 12, 13 and 14 of the block "P" of the lot "Las Marianitas" belonging to the Canton Machala, land of 1,900 m2, but the real condition of the land is 900m2 since the rest turned out to be the canal "El Macho" and part of the road that leads from Machala to Cambio. The scandal perpetrated by the insulting publication ordered by the defendant and printed in the weekly, corresponds to Mr. Eduardo M. Aguila, but not the engineer Marlon Eduardo Aguilar Fallan actor of the cause for moral damage, following due process once the parties They were already cited. The judge of first level gives rise to the claim, in his sound criticism considers that if there was moral damage therefore resolves that the defendant cancels a pecuniary indemnification of ($ 30,000) American dollars of the United States of America. The defendant Maria Eugenia Gutiérrez Giraldo, not agreeing with the decision of the Judge and exercising their right to Defense interposed the appeal on the basis of Article 76 numeral 7 literal m of our Constitution, and makes mention of Article 323 of the Code of Civil Procedure (Valid in the time of beginning of the process) that refers to the Appeal, which is a way of claiming one of the procedural parts before a Superior Judge to revoke or reform a sentence or sentence order. Once the Court of the Civil Chamber of the Provincial Court of Justice of El Oro, resolves to revoke the Judgment of the Judge of First Level, and declares without merit the claim of Mr. Marlon Eduardo Aguilar Fallan the plaintiff of the proceedings interposes the extraordinary appeal of Cassation, based on article 3, first causal of the Law of Cassation. Subsequent to this, through the Sorteo, the Review Chamber of the National Court of Justice is informed, and it is they who qualify the admission or inadmissibility of the appeal, and it should be noted that the appellant must comply with the parameters established in Article 6 of the Law. of Cassation. Therefore, the requirements and formality required by the appeal were not met. That is, it does not comply with the precept of the aforementioned article which refers to the formal requirements. That is why the appeal of Cassation was denied; and because of this, the judgment of the Civil Chamber of the Provincial Court of El Oro was confirmed and this resolution was enforced. The present action ends on May 15, 2017. Within the present case, it should be noted that there was no violation of rights, since the plaintiff, through the evidentiary elements, could not demonstrate the emerging damage and loss of earnings, apart from the fact that no indication was given of their full names and surnames in The Publication of the Weekly. That is why, when considering the appeal, the court, through its sound criticism and assessment of what has already been done in the process, determines that there was no moral damage and therefore revokes the judgment of the First Level Judge.